Playing guitar - Hodge, David 1957- (Indianapolis, Indiana Alpha, a member of Penguin Group (USA), 2013)
A beginner's guide to learning how to play guitar.
Includes bibliographical references (pages 236-237) and index.
Keywords: Guitar -- Methods -- Self-instruction.